Cloning. [Issues in ethics]. - Fielder, J.H (IEEE Engineering in medicine and biology magazine)
It seems ages ago (but it was only 1997) that Dolly, the sheep cloned by Ian Wilmot in Scotland, made headlines all over the world. Using somatic cell nuclear transfer (SCNT), in which genetic material is introduced into an egg from which the nucleus has been removed, Dolly was a copy of the donating sheep. The ethical discussion had already begun, even before a successful mammalian cloning, but Dolly launched an intense debate and calls for legislative bans on human cloning. One of the central ethical questions raised by successful animal cloning is whether human cloning is permissible, and if so, under what conditions. A related question is the therapeutic use of human cloning for research on stem cells. Both reveal complex ethical and political issues; in this space I can only touch on some of them.